2022
DOI: 10.1007/s11739-022-02979-x
|View full text |Cite
|
Sign up to set email alerts
|

6 and 12 month outcomes in patients following COVID-19-related hospitalization: a prospective monocentric study

Abstract: The long-term consequences of COVID-19 in those who recover from acute infection requiring hospitalization have not been defined yet. In this study, we aim to describe the long-term symptoms and respiratory outcomes over 12 months in patients hospitalized for severe COVID-19. In this prospective cohort study, patients admitted to hospital for severe COVID-19 were prospectively followed up at 6 and 12 months after discharge from the Hospital of Fermo, Italy. Patients were interviewed for persisting symptoms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Martino GP et al conducted, in the adult population, using surveys and clinical assessments, where a number of studies documented that many adults recovered after 12 months post-onset. 22,23 However, another study in adults found that certain symptoms such as cognitive problems and dyspnea did not improve. 24 There are few long-term follow-up studies including the paediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Martino GP et al conducted, in the adult population, using surveys and clinical assessments, where a number of studies documented that many adults recovered after 12 months post-onset. 22,23 However, another study in adults found that certain symptoms such as cognitive problems and dyspnea did not improve. 24 There are few long-term follow-up studies including the paediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…159 events of symptom regression were observed. adults post-Covid-19 hospitalization, using telephone follow-up assessments, identified a prevalence of 50% (95% CI 47-53) of post-Covid symptom sequelae in adults and 20% (95% CI [16][17][18][19][20][21][22][23][24] in children at 6-months post-discharge. At 12-months post-discharge, the prevalence was 34% (95% CI 31-37) in adults and 11% (95% CI 8-14), in children.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other symptoms analyzed, including but not limited to rhinitis, sore throut, skin rashes, tinnitus, chest tightness and palpitations/arrhythmias, psychiatric symptoms resolved relatively slow, and may last for more than 12 months ( Kim et al, 2022 ; for reviews see Alkodaymi et al, 2022 ; Renaud-Charest et al, 2021 ) ( Table 1 ). Moreover, reports from longitudinal studies demonstrated that patients may experience exacerbation of some neuropsychiatric symptoms (e.g., problems with mental abilities, anxiety, depression, insomnia, PTSD) after a longer interval ( Buttery et al, 2021 ; Ceban et al, 2022 ; Giurgi-Oncu et al, 2021 ; Martino et al, 2022 ; Renaud-Charest et al, 2021 ) ( Table 1 ). Alarmingly, several studies revealed that around 30% of patients who had recovered from COVID-19 met the criteria of PTSD ( Houben-Wilke et al, 2022 ; Janiri et al, 2021 ; Ju et al, 2021 ; Vagheggini et al, 2022 ) ( Table 1 ).…”
Section: Long Covid: Neuropsychiatric Manifestationsmentioning
confidence: 99%
“…A total of 2517 studies were identified, of which 43 met the inclusion (N = 8858 patients) ( Figure 1 ) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. The majority of studies were from China (14 studies [ 51 , 58 , 59 , 60 , 61 , 64 , 65 , …”
Section: Resultsmentioning
confidence: 99%